New basal taxa of South African Apioninae (Coleoptera: Curculionoidea: Brentidae) - Wanat, Marek (Zootaxa, 2021)
Four new genera, six new species and one new subspecies of the brentid subfamily Apioninae are described from the Republic of South Africa (R.S.A.), all representing ancient fauna with Gondwanan roots. The new genera are: Rhynchitapion gen. n., with Rh. variiforme sp. n. (the type-species) and Rh. pallidum sp. n., Apodytapion gen. n., with A. stepniewskii sp. n., Turnerapion gen. n., with T. pondoense sp. n., and Lepanomidius gen. n., with L. ruthmuellerae sp. n. (the type-species) and L. magdaloides sp. n. The primitive genus Lepanomus Balfour-Browne is re-described and a new subspecies of its type species, Lepanomus crinalis zuluensis ssp. n., is described from north-eastern R.S.A. In addition, Rhynchitapion usambarense sp. n. is described from Tanzania. An identification key to all 12 basal genera of South African Apioninae is presented and their higher systematics is discussed. Three new tribes are proposed in South African Apioninae: Rhynchitapiini trib. n., Apodytapiini trib. n., and Lepanomini trib. n., in addition to the existing basal Antliarhinini Schoenherr, 1823, Tanaini Schoenherr, 1839, Mecolenini Wanat, 2001, Apiomorphini Legalov, 2018, Setapiini Legalov, 2018, and derived Apionini Schoenherr, 1823. A temporary resignation from supertribal division of the subfamily is recommended after discussion.